National surveys of patient experiences with addiction services in Norway: do employees use the results in quality initiatives and are results improving over time? - Haugum, Mona; Iversen, Hilde Hestad; Bjertnaes, Oyvind (Frontiers in Health Services, 2024)
IntroductionThe experiences of patients receiving health care constitute an important aspect of health-care quality assessments. One of the purposes of the national program of patient-experience surveys in Norway is to support institutional and departmental improvements to the quality of local health-care services. This program includes national surveys of patients receiving interdisciplinary treatment for substance dependence performed four times between 2013 and 2017. The aims of this study were twofold: (i) to determine the attitudes of employees towards these surveys and their use of the survey results, and (ii) to identify changes in patient experiences at the national level from 2013 to 2017.Material and methodsEmployees were surveyed one week prior to conducting cross-sectional patient experience surveys. One-way ANOVA and chi-square tests were used to assess differences between years, and content analysis was applied to the open-ended comments.ResultsAround 400 employees were recruited in each of the four survey years, and the response rate varied from 61% to 79%. The employees generally reported a positive attitude towards patient-experience surveys, and 40%–50% of them had implemented quality initiatives based on the results of the patient surveys. The mean score for the question on usefulness was higher than 3 (on a Likert scale from 1 to 5 points) for all four surveys. Many employees provided details about the changes that had been made in open-ended comments. The results from the patient-experience surveys demonstrated positive changes over time.DiscussionThe employees had positive viewpoints towards patient-experience surveys, and around half of them had implemented quality initiatives. This implies that employees find such surveys important, and that patient-experience surveys are regarded as useful and actionable. The surveys of patients showed positive changes in their experiences over time. The most-common target areas reported by employees showed clear improvements in patient experiences at the national level.